Intraoperative Hemorrhagic Shock in Cancer Surgical Patients: Short and Long-Term Mortality and Associated Factors. Issue 5 (November 2020) - Hamon, Annabelle; Mokart, Djamel; Pouliquen, Camille; Guibert, Jean Manuel de; Cambon, Sylvie; Duong, Lam Nguyen; Lambaudie, Eric; Sannini, Antoine; Chow-Chine, Laurent; Bisbal, Magali; Ewald, Jacques; Turrini, Olivier; et al.
ABSTRACT: Background: Management of hemorrhagic shock is well codified by international guidelines. These guidelines are predominantly based on trauma patients. We aimed to evaluate factors associated with 30-day mortality and long-term survival after intraoperative hemorrhagic shock during major oncological surgery. Methods: This retrospective study was conducted in a cancer referral center from January 2013 to February 2018. All adult cancer patients admitted in the operative room for scheduled or emergency oncological surgery associated with an intraoperative hemorrhagic shock were included. Results: Eighty-four patients were included in this study. The 30-day mortality rate was 26% (n = 22), the mean follow-up from the time of ICU admission was 20 months (95% CI, 15–25 months), 39 (46%) patients died during this period. Using logistic regression for multivariate analysis, factors independently associated with 30-day mortality were SAPS II score (odds ratio (OR) =1.056, 95% confident interval (CI) =1.010–1.1041), delta SOFA (SOFA score at day 3 – SOFA score at day 1) (OR= 1.780, 95% CI 1.184–2.677) and ISTH-DIC score (OR = 2.705, 95% CI 1.108–6.606). Using Cox multivariate analysis, factors associated with long-term mortality were delta SOFA (hazard ratio (HR) =1.558, 95% CI 1.298–1.870), ISTH-DIC score (HR = 1.381, 95% CI 1.049–1.817), hepatic dysfunction (HR = 7.653, 95% CI 2.031–28.842), and Charlson comorbidity index (HR = 1.330, 95% CI 1.041–1.699). Conclusion: The worsening of organ dysfunctions during the first 3 days of ICU admission as well as intraoperative coagulation disturbances (increased ISTH-DIC score) are independently associated with short and long-term mortality. Comorbidities (Charlson comorbidity index) and postoperative hepatic dysfunction were independently associated with long-term mortality. Early perioperative bundle strategies should be evaluated in order to improve patient's survival in this specific situation.